The Effect of E-commerce Live Streaming Shopping on Consumers’ Purchase Intention in China-Focusing on Features of Streamers and Contents - Cho, June-Suh; Yang, Liu-Qing (Archives of Business Research, 2021)
In China, online live streaming shopping as a part of e-commerce shows rapid growth, while many sellers can not achieve the economic benefits as expected. This study mainly extracts, analyzes, and examines the general features of e-commerce live streaming shopping, positively affecting consumers’ purchase intentions. Many UGC sellers can obtain some practical ways to output more high-quality content with limited resources. This study places the following nine features as independent hypotheses: streamer’s professionalism, awareness, homogeneity, attractiveness, reliability, contents’ interaction, entertainment, discount, uniqueness, and consumers’ purchase intention taken as a dependent variable. As a result of statistical analysis of the data collected through the survey, all nine hypotheses were adopted.